The Effect of Peripheral Nerve Stimulation on Implicit Motor Learning - Byczynski, Gabriel (Trinity College Dublin. School of Psychology. Discipline of Psychology, 2025)
Applying brain stimulation to motor learning and recovery has been a primary goal since the field was established. Using transcranial alternating current stimulation, electrical current is hypothesized to enter the brain and modulate ongoing neural activity through entrainment. Despite continued effort, there still remains key questions about how stimulation reaches the brain, the inconsistency of its effects, and the optimal delivery parameters and timing. As a novel alternative to traditional methods, stimulating the peripheral nerves such as the vagus and occipital nerves has been shown to similarly alter neural activity, resulting in enhanced neural plasticity and subsequent behavioural improvements. In this thesis, I perform the first investigation using occipital nerve stimulation to modulate motor learning and its subsequent behavioural correlates. I first establish the theoretical basis for the work (chapter 2), in which I review current literature using brain stimulation to modulate motor learning, and posit how traditional protocols might be translated to a peripheral mechanism and approach. I then carried out a meta-analysis of motor learning experiments carried out with functional magnetic resonance imaging, in order to identify online and offline motor learning targets engaged during the learning processes (chapter 3). Together, these chapters form the basis for the empirical works in chapters 4-6. 115 participants were recruited across 4 experiments to perform motor learning tasks concurrent with occipital nerve stimulation. In experiment 1, I establish that occipital nerve stimulation produces frequency-specific modulation of motor learning, operationalized as motor skill. In experiment 2, I show that lidocaine/prilocaine anaesthetic reduces the effect of occipital nerve stimulation on motor learning modulation, supporting a transcutaneous mechanism. In experiment 3, I illustrate electroencephalographic changes in resting state neural activity and event-related potentials consistent with altered GABA levels in the engaged motor cortex. I also identify pupillometry changes consistent with the involvement of the locus-coeruleus noradrenaline system, and behavioural changes persisting 24 hours later. In experiment 4, I conclude by identifying modulated cortical excitability using transcranial magnetic stimulation, further supporting changes in cortical plasticity. Together, these findings suggest that occipital nerve stimulation modulates motor learning in a frequency-specific manner via a transcutaneous route, and that these changes involve altered neural plasticity, possibly instigated by GABA and noradrenaline activity. This work presents a novel approach to modulating motor learning, and supports further research for its use in motor learning, rehabilitation, and recovery.
APPROVED
Keywords: Motor learning; Brain stimulation; Nerve stimulation; EEG